Health behaviors, nutritional status, and anthropometric parameters of Roma and non-Roma mothers and their infants in the Czech Republic - Rambousková, Jolana; Dlouhý, Pavel; Krízová, Eva; Procházka, Bohumír; Hrncírová, Dana; Andel, Michal (Journal of nutrition education and behavior, 2009)
OBJECTIVE: To compare maternal health behaviors, maternal nutritional status, and infant size at birth of Romas and non-Romas in the Czech Republic. DESIGN: Maternal interviews and food frequency questionnaire, maternal blood samples, physical measurements of mothers and infants. SETTING: Hospital, maternal/child care center; 2-4 days postpartum. PARTICIPANTS: 76 Roma mothers and 151 mothers from the majority population. MAIN OUTCOME MEASURES: Infant length/weight; maternal height/weight; weight gain during pregnancy; duration of pregnancy; maternal smoking habits; dietary intake; use of food supplements during pregnancy; and maternal blood levels of folate, beta-carotene, retinol, and alpha-tocopherol. ANALYSIS: Comparison of ethnic groups by 2-sample Wilcoxon test, chi-square, Fischer's exact test, relative risk, and analysis of variance (ANOVA). RESULTS: Pregnancy duration was about 1 week shorter in Roma women (P < .001), and their infants had lower birth weight (P < .001) and shorter length (P < .001). Prevalence of smoking was significantly higher among Roma mothers (P < .001). Roma women used food supplements less frequently than non-Roma women (P < .001) and had significantly lower mean blood concentrations of folate (P < .001), beta-carotene (P < .001), retinol (P < .02), and alpha-tocopherol (P < .02). CONCLUSIONS AND IMPLICATIONS: The nutritional status of Roma mothers is worse than that of mothers from the majority Czech population. The dietary and smoking habits of pregnant Roma women should be of special concern to family doctors, obstetricians, nutrition educators, and social workers.
Keywords: novorozenec; Infant, Newborn; tělesné váhy a míry; stravovací zvyklosti; kyselina listová; nutriční stav; Pregnancy; Humans; porodní hmotnost; Female; Folic Acid; analýza rozptylu; Romové; Analysis of Variance; zdravé chování; lidé; Roma; Nutritional Status; Interviews as Topic; ženské pohlaví; Maternal Health Services; Birth Weight; těhotenství; služby zdravotní péče o matku; potravní doplňky; Czech Republic; Dietary Supplements; Smoking; Česká republika; Feeding Behavior; kouření; rozhovory jako téma; Body Weights and Measures; Health Behavior